Estimation of desired feed intake for growth and reproductive organ development in pre-laying hens - Bendezu, Hilda Palma [UNESP]; Sakomura, Nilva Kazue [UNESP]; Malheiros, Euclides Braga [UNESP]; De Paula Dorigam, Juliano Cesar [UNESP]; Da Silva, Edney Pereira [UNESP]; Reis, Matheus De Paula [UNESP] (Csiro Publishing, 2019)
The objective of the present study was to describe the growth of reproductive organs and, on the basis of this information, predict feed intake during the pre-laying phase of laying-type pullets and to evaluate the results of the models. Ninety-six ISA-Brown pullets from 15 to 28 weeks of age were used in the first experiment. The weights of the birds with and without feathers, ovaries and oviducts were measured, and samples were taken to analyse dry matter, gross energy and crude protein. Seventy-six ISA-Brown and 76 Hy-Line pullets from 15 to 24 weeks of age were used in the second experiment. Feed intake was measured daily for each hen until the first egg was laid. The energy for maintenance (EEM) was calculated on the basis of the actual protein content and protein weight at maturity. The effective energy (EE) requirement was calculated as EER = EEM + 50 deposition of protein (DP) + 56 deposition of lipids (DL). Feed intake was calculated by dividing the EE requirement by the EE content in the feed. The simulation of feed intake overestimated values of 0.41 g/day (P > 0.05) and 2.65 g/day (P < 0.001) for Hy-Line and ISA-Brown respectively. A significant linear bias was observed for Hy-Line (P < 0.001) but not for ISA-Brown (P > 0.05). The assessment of the results indicated that the models for predicting feed intake were more accurate and less precise for Hy-Line than for ISA-Brown. Thus, there was an agreement between the calculated and measured values for feed intake, which shows that the models provide a true estimation of feed intake during the pre-laying phase.
Keywords: genetic potential; nutrient requirement; nutrition model; poultry; pullets